АВТОРСКИЙ МЕТАЯЗЫК В СТИЛИСТИКЕ ХУДОЖЕСТВЕННОГО ТЕКСТА (Филолошки студии, 2019)
The article deals with the interpretation of particular lexical items in the art text. The denotative and connotative components in the structure of intralexicographic article are analyzed from the perspective of the author’s creative intention. It is concluded the author’s way of lexicography organical supplement of the main content, enhancing the process and relaying the collective experience of native speaker, and thus expanding the boundaries of linguistic and cultural space of the text.